VARIASI TEKNIK PENERJEMAHAN: STUDI KASUS PEMINJAMAN, KALKE DAN AMPLIFIKASI DALAM TEKS ARAB-INDONESIA - Nashrul A'aly Ramadhani; Silma Salsa Bila (PT. Hasba Edukasi Mandiri, 2025)
This study aims to identify and analyze the variations of translation techniques, particularly borrowing, calque, and amplification, in Arabic texts translated into Indonesian. The research employs a qualitative approach using library research as the primary method of data collection. The data sources are drawn from various Arabic-Indonesian translated documents, including religious texts, academic literature, and popular writings. The findings indicate that borrowing is predominantly used for shar’i terms that are widely recognized by Indonesian readers, such as zakat, shalat, and hajj. Calque is used to preserve the structural form of Arabic expressions, such as Bayt al-Hikmah being rendered as Rumah Hikmah (House of Wisdom). Meanwhile, amplification is often applied to clarify implicit meanings within Arabic, such as in the phrase